Pengaruh Pemahaman Operasional Bank Syariah dan Penerapan Qanun Lembaga Keuangan Syariah Di Aceh Terhadap Minat Berinvestasi Pada Saham Bank Syariah (Studi Kasus Nasabah RHB Sekuritas Aceh) - Maulidan, Armad; Ismuadi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This research is important to do to see the effect of the implementation of the qanun of Islamic financial institutions that have been implemented in Aceh on the interest in investing in Islamic bank shares because the implementation of the qanun has a positive impact on Islamic banks. The research method used is a quantitative research method, the data used are primary data using a questionnaire survey, the results of this study indicate that the operational understanding of Islamic banks has an effect on interest in investing in Islamic bank shares but is not significant and the application of the qanun of Islamic financial institutions in Aceh has an effect on interest investing in Islamic bank shares is very significant while simultaneously having a significant effect on interest in investing in Islamic bank shares.